(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The conceptualized term of rural – urban divide exaggerates the gap of inequality in the sense of education, income distribution, quality of life, modern amenities and technological advancement. In India inequalities in education and learning achievement is increasing gradually due to rural-urban divide paradigm. At present, the world is witnessing an unprecedented human health pandemic COVID-19 which compels us to rethink in all aspects of human life including educational facilities. During COVID-19 imbalance and inequalities are clearly manifested in terms of unequal access to visual learning and online facilities in rural areas. Most of the students in rural areas are affected and deprived of attending online classes due to no accessibility of technology. Socio-economic condition and source of livelihood of rural households are shaken due to the COVID-19 pandemic and it exerts negative impact on children’s education and mental health as well in comparison to the urban areas. Specially in Assam, it is clearly visible that education and learning process are jeopardized and students committed suicide due to lack of android mobile for e-learning. This rural- urban divide intensifies the inequalities in education and learning process. In the present research work the investigators attempts to highlight the inequalities in education due to rural-urban divide. Descriptive survey method has been applied and purposive sampling technique was used while selecting sample for collecting data. The analysis has been done on the basis of descriptive statistics.